Penyuluhan Hukum Untuk Penggiat Usaha Kecil dan Menengah di Kecamatan Kebayoran Baru Jakarta Selatan - Chrisbiantoro, Chrisbiantoro; Untoro, Utami Yustihasana (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2023)
Being aware of the law and then being able to understand rights and obligations before the law and ensuring legal protection for Micro, Small and Medium Enterprises (MSMEs) activists is the ideal condition that we all hope for to create the growth of MSMEs in Indonesia. It is clear that MSMEs activists as an important component in economic development in Indonesia need legal certainty and protection. For the role of all parties, one of them is academician, namely lecturers or instructors, it is very necessary. Through the spirit of the Tridharma of University, academician can contribute through legal counseling programs to ensure that legal protection is given to MSMEs activists. Through counseling for MSMEs activists in cooperation with the Yayasan Inspirasi Indonesia Membangun (YIIM) in the Kebayoran Baru District area, South Jakarta Municipality, it is hoped that this will become a good portfolio for the contribution of academician to strengthening MSMEs, especially legal literacy so that MSMEs activists are able to identify and find solutions to various cases encountered in daily life.